The charity of nations : the political economy of foreign aid - Wall, David; Cohen, Benjamin J. (London : Macmillan, 1973)
This book is centred on a discussion of the motives for aid giving, the domestic politics of decision making on aid, and the debates on its forms and channels. The book concludes that 'the prime motive for aid is self-interest', the aims of aid-givers including the guaranteeing of increased supplies of food and raw materials and insurance against war, disruption of sources of supply and loss of face in world.
Includes index.
Includes bibliographical references: p. 169-173.
lje 02/10/2018
Loans
Keywords: Economic assistance